2020
DOI: 10.1097/ju.0000000000000579
|View full text |Cite|
|
Sign up to set email alerts
|

Testis Sparing Surgery of Small Testicular Masses: Retrospective Analysis of a Multicenter Cohort

Abstract: We evaluated possible factors predicting testicular cancer in patients undergoing testis sparing surgery. Materials and Methods: We retrospectively analyzed the records of all patients who underwent testis sparing surgery for a small testicular mass at a total of 5 centers. All patients with 1 solitary lesion 2 cm or less on preoperative ultrasound were enrolled in the study. Testis sparing surgery consisted of tumor enucleation for frozen section examination. Immediate radical orchiectomy was performed in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 19 publications
(29 reference statements)
6
47
1
Order By: Relevance
“…At 13.5 mm, we report a considerably higher best cutoff for lesion diameter based on our series of 99 enucleation procedures (53% sensitivity, 85% specificity, 63% PPV, 79% NPV). Moreover, we found 21.8% of all lesions with a size ≤ 10 mm (12 of 55) to be malignant, which is a considerably higher rate than the 10% reported by Gentile et al [14]. Applying the confirmed cutoff of 8.5 mm by Gentile et al [14], we obtained similar results concerning the diagnostic accuracy (75% sensitivity, 54% specificity, 44% PPV, 82% NPV).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…At 13.5 mm, we report a considerably higher best cutoff for lesion diameter based on our series of 99 enucleation procedures (53% sensitivity, 85% specificity, 63% PPV, 79% NPV). Moreover, we found 21.8% of all lesions with a size ≤ 10 mm (12 of 55) to be malignant, which is a considerably higher rate than the 10% reported by Gentile et al [14]. Applying the confirmed cutoff of 8.5 mm by Gentile et al [14], we obtained similar results concerning the diagnostic accuracy (75% sensitivity, 54% specificity, 44% PPV, 82% NPV).…”
Section: Discussionsupporting
confidence: 78%
“…Actually, the patients involved in this study had testicular tumors ≤ 20 mm in diameter. Gentile et al [14], who also examined patients with testicular masses less than 20 mm, found that the smaller a lesion, the less likely it was to be malignant, and reported a best cutoff of 8.5 mm [14]. At 13.5 mm, we report a considerably higher best cutoff for lesion diameter based on our series of 99 enucleation procedures (53% sensitivity, 85% specificity, 63% PPV, 79% NPV).…”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations
“…With the evergrowing number of incidentally detected cases of small testicular neoplasms, it became clear that many of these cases are of benign nature and would, therefore, require only a conservative surgical approach or even no surgery at all (Dieckmann et al 2013;Paffenholz et al 2018). However, approximately 15-20% of all small testicular neoplasms < 1 cm still represent malignant germ cell tumours (Gentile et al 2020), and therefore the general recommendation for surveillance of small tumours has remained a matter of debate (Ates et al 2016;Kern et al 2020;Laclergerie et al 2018).…”
Section: Discussionmentioning
confidence: 99%